Between sessions: The crucial role of parent engagement in treatment. Issue 7 (July 2016) - Laptook, Rebecca
Abstract : When treating psychological disorders in childhood, it is good practice to extend the assessment of the child to the broader family context, as a child does not exist alone but rather functions as part of his or her family. In understanding the nature of the concerns for which a parent has brought a child in for treatment, therapists may explore parent‐child dynamics and sibling relationships, parenting behaviors and practices, and the role of parental psychopathology in addition to school and social dynamics. In short, to conceptualize psychological concerns, it is helpful to have a better understanding of a child's environment and how that child functions within different systems.